Organic Molecules Mimic Alkali Metals Enabling Spontaneous Harpoon Reactions with Halogens - Cao, Wenjin; Wang, Xue‐Bin (Chemistry : a European journal, 2024)
The harpoon mechanism has been a milestone in molecular reaction dynamics. Until now, the entity from which electron harpooning occurs has been either alkali metal atoms or non‐metallic analogs in their excited states. In this work, we demonstrate that a common organic molecule, octamethylcalix[4] pyrrole (omC4P), behaves just like alkali metal atoms, enabling the formation of charge‐separated ionic bonding complexes with halogens omC4P+ ⋅ X− (X=F−I, SCN) via the harpoon mechanism. Their electronic structures and chemical bonding were determined by cryogenic photoelectron spectroscopy of the corresponding anions and confirmed by theoretical analyses. The omC4P+ ⋅ X− could be visualized to form from the reactants omC4P+X via electron harpooning from omC4P to X at a distance defined by the energy difference between the ionization potential of omC4P and electron affinity of X. Octamethylcalix[4]pyrrole (omC4P) behaves like alkali metals and reacts with halogens (X) via the harpoon mechanism to form charge‐separated omC4P+ ⋅ X− complexes.harpoon reactionlong range electron transferphotoelectron spectroscopy